The Impact of Transformational Leadership, Employee Satisfaction, and Employee Engagement on Employee Loyalty - Cahyadi Wiguna, I Kadek Dwita; Adhi Tenaya, I Pande; Wardana, I Made Aditya (Akademi Komunitas MAPINDO, 2024)
Employee loyalty is an important part of managing a hotel business. So antecedents of loyalty are needed, suchas transformational leadership, employee engagement, and employee satisfaction. This research examines theinfluence of transformational leadership, employee engagement, and employee satisfaction on employeeloyalty. This research involved employees at four-star hotels with a total of 261 respondents. The data collectedwas analyzed using multiple linear regression analysis with the IBM SPSS 27 program. Research findings showthat transformational leadership does not affect employee loyalty. Meanwhile, employee engagement andemployee satisfaction significantly increase employee loyalty. Some of the limitations of this research are thatthere is no separation between back office employees and frontliners so it is difficult to determine the level ofaccuracy of the perceptions given. Apart from that, the data collection method uses self-assessment so data biasis very high.Keywords: Transformational Leadership, Employee Engagement, Employee Satisfaction and EmployeeLoyalty